2012
DOI: 10.1007/s00586-012-2414-9
|View full text |Cite
|
Sign up to set email alerts
|

Instability of treated vertebrae after balloon kyphoplasty causing paraparesis in osteoporotic vertebral compression fracture: a report of two cases

Abstract: PurposeTo describe two unique cases of osteoporotic vertebral compression fracture (OVCF) treated with balloon kyphoplasty (BKP) that were complicated by spinal instability and resultant lower extremity paraparesis.MethodsKyphoplasty was performed in two patients with OVCF that had persistent back pain despite a course of conservative care. Immediately following BKP, both patients had a marked improvement in back pain. However, they developed progressive bilateral lower extremity weakness. Lateral spine flexio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Recently, interest has increased in the mortality and morbidity of patients who undergo spinal surgery [ 18 , 19 ]. Additionally, numerous reports have surfaced for comparative studies of surgical procedures for OVF; these have focused on surgical invasiveness and complications [ 20 ]. By contrast, the postoperative outcome of pain and survival of patients with an insufficient bony union after OVF surgery remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, interest has increased in the mortality and morbidity of patients who undergo spinal surgery [ 18 , 19 ]. Additionally, numerous reports have surfaced for comparative studies of surgical procedures for OVF; these have focused on surgical invasiveness and complications [ 20 ]. By contrast, the postoperative outcome of pain and survival of patients with an insufficient bony union after OVF surgery remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…11 Furthermore, paraparesis has been reported to occur due to instability after BKP. 12 We also observed one case with delayed palsy after BKP in our institution that needed additional decompression and fusion surgery. In other words, the instability that occurs because of the OVF remains after BKP (Fig.…”
Section: Introductionmentioning
confidence: 62%
“…Past literature previously reported that instability remains after balloon kyphoplasty. 10 Ohba et al 12 reported that instability of the treated vertebrae after balloon kyphoplasty caused paraparesis. In addition, Kim et al 11 reported that the incidence of recompression in treated vertebrae was 12.5%.…”
Section: Discussionmentioning
confidence: 99%
“…[18,19] Additionally, numerous reports have surfaced for comparative studies of surgical procedures for OVF; these have focused on surgical invasiveness and complications. [20] By contrast, the postoperative outcome of pain and survival of patients with an insu cient bony union after OVF surgery remains largely unknown. Although the present study showed that the VAS scores for both the lumbar spine and leg were signi cantly improved one year after surgery compared to scores at the time of hospital admission, those scores may not be meaningful clinically.…”
Section: Discussionmentioning
confidence: 99%